Applying the energy cultures framework to understand energy systems in the context of rural sustainability transformation. (February 2020) - Klaniecki, Kathleen; Duse, Ioana Alexandra; Lutz, Lotte M.; Leventon, Julia; Abson, David J.
Abstract: Addressing the threat of global climate change will require large-scale transformation of our energy systems. Scholars are increasingly calling for a more systemic approach to studying energy transitions—one that incorporates human dimensions such as behaviors, attitudes, perceptions, and preferences. Drawing on an exploratory representative study (n = 379 surveys) conducted in the Pogány-havas microregion of eastern Transylvania, Romania, we employ Stephenson et al.'s Energy Cultures Framework to describe and discuss the social and material energy system of the region. We highlight the interactions between norms, energy practices and material culture, as well as external influences that are shaping the energy system. We discuss attitudes towards energy conservation and acceptability of community renewable energy schemes. Based on our findings, we define the dominant energy culture of the region and highlight elements of the system that are either reinforcing the status quo or shaping a more sustainable energy culture. We discuss implications for increasing the efficiency of the energy system of this region and factors that could inform energy policies and sustainability interventions. We conclude by situating our research within a larger narrative of rural energy transitions and discuss the value of a systems approach when undertaking energy systems research. Highlights: The social and material energy culture of a rural region in Transylvania is explored. Interactions between norms, energy practices, and material culture are highlighted. The paper distinguishes factors enabling or constraining the current energy culture. Findings are related to energy policies and sustainability interventions. Rural energy interventions must focus on a reliable and affordable energy supply.